2007
DOI: 10.1038/sj.leu.2404913
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3+ regulatory T cells in cutaneous T-cell lymphomas: association with disease stage and survival

Abstract: FOXP3 is a unique marker for CD4 þ CD25 þ regulatory T cells (Tregs). In solid tumours, high numbers of Tregs are associated with a poor prognosis. Knowledge about the implications of Tregs for the behaviour of haematological malignancies is limited. In this study, skin biopsies from 86 patients with mycosis fungoides (MF) and cutaneous T-cell lymphoma (CTCL) unspecified were analysed for the expression of FOXP3 on tumour cells and tumour-infiltrating Tregs. Labelling of above 10% of the neoplastic cells was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
4
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 37 publications
8
120
4
5
Order By: Relevance
“…Since the amount of FOXP3 + cells did not show association with any of the studied parameters: patient age or gender, tumor thickness, location, histological type, ulceration and, most importantly, the outcome of the disease, as mentioned above, FOXP3 + cell infiltration in the primary tumor does not seem to have a significant impact on the course of the disease in cutaneous melanoma. Previous studies aiming at the clinical relevance of tumor-infiltrating Tregs have given rise to contradictory results, showing correlation with poor outcome in some cancer types [5][6][7][8][9] but no association or even correlation with improved survival in others [10][11][12][13][14][15][16][17]21]. It could be suggested that each tumor type behaves differently in this context [4], depending perhaps on other players on the scene of antitumor immune reactions and their complex functional interrelationships with Tregs as well as with tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the amount of FOXP3 + cells did not show association with any of the studied parameters: patient age or gender, tumor thickness, location, histological type, ulceration and, most importantly, the outcome of the disease, as mentioned above, FOXP3 + cell infiltration in the primary tumor does not seem to have a significant impact on the course of the disease in cutaneous melanoma. Previous studies aiming at the clinical relevance of tumor-infiltrating Tregs have given rise to contradictory results, showing correlation with poor outcome in some cancer types [5][6][7][8][9] but no association or even correlation with improved survival in others [10][11][12][13][14][15][16][17]21]. It could be suggested that each tumor type behaves differently in this context [4], depending perhaps on other players on the scene of antitumor immune reactions and their complex functional interrelationships with Tregs as well as with tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the prognostic role of tumor-infiltrating Tregs are inconclusive; while in some cancer types their increased level has been correlated with poor outcome, as in the case of ovarian, breast, pancreatic and hepatocellular carcinomas [5][6][7][8][9], in others including prostate and renal cancers no significant associations were found [10,11], and in the case of head and neck carcinomas, colorectal cancer, as well as in several lymphoma types a marked infiltration by Tregs showed correlation with improved survival [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were drawn from the archives of the Departments of Pathology at Rigshospitalet (Copenhagen University Hospital) and Bispebjerg Hospital and have been described in detail elsewhere. 48 For immunohistochemistry, 47 cases were selected for analysis. Fourteen patients had MF with patches, and 21 had plaques.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, FoxP3 expression alone, particularly at low-intermediate levels, as observed in activated T cells and in some patients with CTCL, is insufficient evidence to support the claim that clonal T cells in MF or SS are Treg-derived, particularly considering the observation that conventional T cells may acquire a similar Treg-phenotype when cultured under similar conditions [24,25]. Subsequent histologic analyses of FoxP3 expression by immunohistochemical staining demonstrate that malignant T cells in CTCL lesions do not express FoxP3 to any significant degree [26,27]. As FoxP3 expression is not entirely specific for Treg cells, the definition of ''Treg cells'' has been, at least in part, a functional one.…”
Section: Cell Of Originmentioning
confidence: 98%